70-th anniversary of Volodymyr Mykolaiovych Pavlovych - Institute for Nuclear Research (Ядерна фізика та енергетика)
Brief biography and scientific achievements of Volodymyr Mykolaiovych Pavlovych in relation with his 70-th anniversary